The role of Islamic social finance towards alleviating the humanitarian crisis in North-East Nigeria - Ibrahim Mohammed Lawal; Jiddah M.A. Ajayi (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
This paper seeks to examine the role of Islamic social finance towards alleviating the humanitarian crisis in North East Nigeria. The paper revealed the various conceptual definitions of Islamic social finance, its various instruments, update on humanitarian situation. A modified revenue function model was adopted. The study revealed that zakat potentials in Nigeria is estimated to be between USD 8,776.5-USD 21,160.99 million which is alone adequate to fill the humanitarian funding gap. More so, Sadaqah and Waqf was analyzed based on the number of active Telecoms line subscribers and the population statistics of citizens within the ages of 15-69yrs and that If N20 is paid weekly at a 5% level of cash collection error rate, a total amount of about N162b and N106b could be realized yearly respectively which can be used to bridge certain sectors of humanitarian needs in areas of housing, primary health care centres, water, food, empowerment etc. Likewise, the said funds can still be used for investment purposes in areas like mudaraba term deposit, sukuk, stock etc most especially funds realized from cash waqf. The study concluded that by adequately combining the Islamic social finance tools while adopting technology in its collection process & monitoring, it will effectively bridge the humanitarian funding gap as well as resettling and empowering the IDPs. The study recommends legislation of act setting up zakat/waqf, public awareness should be properly done, use of crowd funding approach